An insight into the promotional effect on Fe-Co bimetallic catalyst in the Fischer Tropsch reaction: A DRIFTS study. (15th September 2020) - Sonal,; Pant, Kamal K.; Upadhyayula, S.
Graphical abstract: Highlights: The promotional effect of Ru and Rh on the FT activity was studied via DRIFTS study. Different adsorption trends of CO over Rh and Ru promoted catalyst were observed. 0.5Rh/10Fe/20Co/SiO2 catalyst was observed as an optimum performing catalyst. Rh promoted catalyst results in 75% CO conversion and 67% C5+ selectivity. Abstract: Effect of noble metal promotion over the Fischer Tropsch activity of 10Fe/20Co/SiO2 (weight %) bimetallic catalyst was investigated via a detailed experimental study. The addition of noble metal can promote the structural as well as electronic properties of the catalyst, thus affect the activity and product selectivity of the catalyst. The catalyst 10Fe/20Co/SiO2 was impregnated with varying Rh and Ru loading (0.05 to 1 wt%), and their activity was tested under identical reaction conditions. Different catalyst characterization techniques viz. Brunauer–Emmett–Teller surface area, transmission electron microscope, X-ray diffraction, temperature-programmed reduction, O2 titration and H2 pules chemisorption, were used to study the promotional effect on the catalyst structure. The increased metal loading (Ru and Rh) increases the metal dispersion and the reducibility, resulting in higher H2 chemisorption uptake. Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) was used to investigate the adsorption properties of CO on Rh and Ru promoted catalyst with CO and H2 as probe molecules. The correlation was observed between DRIFTS results and experimental results obtained from the laboratory reactor. A clear distinction between the adsorption trend of CO over Ru and Rh promoted catalyst was observed. Also, the increased intensity of bridge bonded CO was observed, resulting in higher wax formation in the Ru promoted catalyst. The promoted catalysts (0.5Ru/10Fe/20Co/SiO2 and 0.5Rh/10Fe/20Co/SiO2 ) were compared with unpromoted bimetallic catalyst at varying temperatures (220–280 °C). The findings also suggest that Rh promotion enhances the water–gas shift reaction, which significantly changes the H2 /CO ratio and the overall catalyst performance.